Reconstructing the History and the Effects of Mechanization in a Small-Scale Fishery of Flores, Eastern Indonesia (1917–2014) - Ramenzoni, Victoria C. (Frontiers in Marine Science, 2017)
The number of studies on small-scale fishing communities has grown considerably over the past 30 years. Evidence on how the process of mechanization and technological expansion has affected traditional small-scale fishers in peripheral regions, however, is less abundant. For areas like Eastern Indonesia that are now facing important challenges in governance and resource degradation, lack of information impairs the design of long-term environmental solutions. This article explores the changes in fishing participation and per capita seafood intake in a small-scale fishery in Flores, Eastern Indonesia over the past 100 years (1917–2014). By combining multiple sources of information (ethnographic, observational, nutritional, and historical) to reconstruct the story of stocks, fishing effort, and consumption of marine products, long-term trajectories, and trends in resource use practices are identified. Findings underline that mechanization and commercialization can have dire repercussions on food security and job stability within small-scale fishing sectors, especially if these processes are not part of comprehensive community development programs. The article concludes that understanding the outcomes of mechanization at the fringes of more centralized systems is essential to navigate the trade-offs among poverty reduction, economic growth, and environmental degradation.